2015
DOI: 10.1111/adb.12294
|View full text |Cite
|
Sign up to set email alerts
|

Rat‐strain dependent changes of dendritic and spine morphology in the hippocampus after cocaine self‐administration

Abstract: We previously showed that cocaine self-administration increases spine density in CA1 hippocampal neurons in Lewis (LEW) but not in Fischer 344 (F344) rats. Dendritic spine morphology is intimately related to its function. Thus, we conducted a 3D morphological analysis of CA1 dendrites and dendritic spines in these two strains of rats. Strain-specific differences were observed prior to cocaine self-administration: LEW rats had significantly larger dendritic diameters but lower spine density than the F344 strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Taking both results together (regarding synaptic shape and size), cocaine-SA seems to induce an increase in the synaptic surface of axospinous AS, increasing both the proportion of synapses with more complex shapes and the size of macular synapses. In a previous study, we observed an increase in the proportion of larger dendritic spines in the Lewis rat CA1 after cocaine-SA 14 . We can therefore speculate that cocaine-SA causes an increase in synaptic activity and that this may induce the growth of macular synapses and, in some cases, lead to deep indentations and perforations appearing as the postsynaptic density (PSD) becomes larger (Supplementary figure 2).…”
Section: Synaptic Shape Synaptic Size and Curvaturementioning
confidence: 68%
See 2 more Smart Citations
“…Taking both results together (regarding synaptic shape and size), cocaine-SA seems to induce an increase in the synaptic surface of axospinous AS, increasing both the proportion of synapses with more complex shapes and the size of macular synapses. In a previous study, we observed an increase in the proportion of larger dendritic spines in the Lewis rat CA1 after cocaine-SA 14 . We can therefore speculate that cocaine-SA causes an increase in synaptic activity and that this may induce the growth of macular synapses and, in some cases, lead to deep indentations and perforations appearing as the postsynaptic density (PSD) becomes larger (Supplementary figure 2).…”
Section: Synaptic Shape Synaptic Size and Curvaturementioning
confidence: 68%
“…Numerous studies have found that a variety of drugs of abuse produce several morphological modifications of the pyramidal neurons, including the dendritic spines, which represent the main postsynaptic target of excitatory glutamatergic synapses of the cerebral cortex 6 . These changes are found in different brain regions including the frontal cortex, hippocampus and the nucleus accumbens (e.g., 7,8,9,10,11,12,13,14 ). Previous studies in our laboratory have shown that cocaine-induced changes in the hippocampus depend on the rat strain; specifically, an increase in the dendritic spine density and the proportion of larger spines after cocaine self-administration (SA) in Lewis rats 13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After cocaine SA, proximal dendritic volume, dendritic surface area, and spine density were increased in LEW strain, where also an increased percentage of larger spines was observed. In contrast, F344 rats showed decreased spine head volume after cocaine SA (Selvas et al, 2015 ).…”
Section: Structural Plasticity and Differences In Genes Expressionmentioning
confidence: 99%
“…Dendritic spine morphology has become a central focus in research in the fields of learning and memory, aging, and neurodegenerative diseases (for review see Dickstein et al, 2007;Hara et al, 2012;Dickstein et al, 2013) as well as other neuropsychiatric disorders such as autism (Hung et al, 2008;Hutsler and Zhang, 2010;Durand et al, 2012;Phillips and Pozzo-Miller, 2015), schizophrenia (Hayashi-Takagi et al, 2011;Ramos-Miguel et al, 2015), and addiction (Maze et al, 2010;Selvas et al, 2015) as they are an integral component of excitatory synapses. Excitatory synapses comprise the majority of connections in the central nervous system and play a vital role in learning, memory, and cognition.…”
Section: Background Informationmentioning
confidence: 99%